2019
DOI: 10.1039/c8cs00620b
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometallated tridentate platinum(ii) arylacetylide complexes: old wine in new bottles

Abstract: Platinum(ii) cyclometallated pincer complexes with an alkynyl ligand in the fourth coordination site display excellent luminescent properties. By manipulation of the pincer and the alkynyl ligand their luminescence can be fine-tuned for opto-electronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 50 publications
2
89
1
Order By: Relevance
“…In recent decades, phosphorescent transition-metal complexes (PTMCs) play a crucial role in the fields of advanced functional materials. [1][2][3][4][5][6][7][8] Quite different from the traditional fluorescent materials with the light emission from the singlet states, PTMCs are triplet emitters. [9][10][11][12][13][14] Since Forrest and coworkers successfully realized the first phosphorescent organic should be well noted that many phosphorescent manganese(II) complexes also exhibit ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, phosphorescent transition-metal complexes (PTMCs) play a crucial role in the fields of advanced functional materials. [1][2][3][4][5][6][7][8] Quite different from the traditional fluorescent materials with the light emission from the singlet states, PTMCs are triplet emitters. [9][10][11][12][13][14] Since Forrest and coworkers successfully realized the first phosphorescent organic should be well noted that many phosphorescent manganese(II) complexes also exhibit ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, phosphorescent transition‐metal complexes (PTMCs) play a crucial role in the fields of advanced functional materials. [ 1–8 ] Quite different from the traditional fluorescent materials with the light emission from the singlet states, PTMCs are triplet emitters. [ 9–14 ] Since Forrest and co‐workers successfully realized the first phosphorescent organic light‐emitting device (OLED) in 1998, [ 1 ] phosphorescent transition‐metal complexes, especially for noble metal‐based ones (e.g., iridium(III), platinum(II), etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that CuX (X = Cl, Br, I) salts react with ethynylpyridine-based ligands in dichloromethane to form ISSN 2056-9890 coordination-driven self-assembled tetrahedral Cu I complexes; however, oxidation to form Cu II species is also possible. We have a long-standing interest in the design and development of functional ethynyl-based carbocyclic and heterocyclic ligands and their transition metal complexes (Haque et al, 2018;Haque et al, 2019a). In the past, we have reported several dimeric, tetrameric, and polymeric Cu I complexes supported by ethynylpyridine-based ligands.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Because of these features, these materials have shown potential applications in optoelectronics, biologicals, catalysis, sensing and other areas. 14,20,21 Comprehensive studies on poly-ynes and poly(metalla-ynes) by us and others [21][22][23] have shown that the π-conjugation and the extent of delocalization in such systems are highly dependent on the geometry, the ligand environment around the metal centre and the presence or absence of other metal ions. 10,24 For instance, we have recently shown that the incorporation of a second metal ion such Re(I) 25 and Eu(III) 26 is an effective strategy to fine tune their absorption and emission profiles.…”
Section: Introductionmentioning
confidence: 99%